2014
DOI: 10.1155/2014/958524
|View full text |Cite
|
Sign up to set email alerts
|

Association between Disease‐Specific Quality of Life and Complementary Medicine Use in Patients with Rhinitis in Taiwan: A Cross‐Sectional Survey Study

Abstract: Rhinitis is a common medical condition and can seriously impact patients' quality of life. The objective of this study was to investigate the association between disease-specific quality of life and use of complementary and alternative medicine (CAM) modalities among Taiwanese rhinitis patients. A cross-sectional survey was undertaken at the outpatient department of otolaryngology in a medical center in Taiwan. Sociodemographic information, disease-specific quality of life (Chinese version of the 31-item Rhino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Recent studies have suggested that middle-aged to older adults tended to seek different kinds of CAM to help them improve the harmony between their mind, body, and spirit [ 6 , 18 , 24 ]. Middle-aged adults, especially women and those with a higher education level, tend to search for more valuable sources of information to use different kind to CAMs and share their experiences with their friends [ 20 , 30 , 34 ]. In Taiwan, the prevalence rate for CAM use in the previous 12 months was 38 to 86% among people aged 18 years and above to maintain their health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have suggested that middle-aged to older adults tended to seek different kinds of CAM to help them improve the harmony between their mind, body, and spirit [ 6 , 18 , 24 ]. Middle-aged adults, especially women and those with a higher education level, tend to search for more valuable sources of information to use different kind to CAMs and share their experiences with their friends [ 20 , 30 , 34 ]. In Taiwan, the prevalence rate for CAM use in the previous 12 months was 38 to 86% among people aged 18 years and above to maintain their health.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was developed in a 3-step procedure of preliminary drafting according to our previous published paper [ 20 ], revision based on five expert opinions, and final editing. Questionnaires on CAM uses within the past three months was classified into six categories according to the classification system for various modalities from the National Center for Complementary and Integrative Health (NCCIH) [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TCM is the most popular complementary treatment used for allergic disease in Asian countries (Man, 2009;Hon et al, 2015;Yonekura et al, 2017). According to our previous survey, about 34% patients who visited our department for rhinological disorders had received TCM treatment (Koo et al, 2014). Although there is evidence supporting the efficacy of TCM for treatment of AR, the methodology of these clinical trials was frequently inadequate.…”
Section: Discussionmentioning
confidence: 99%